Fractional exhaled nitric oxide as a potential biomarker for radiation pneumonitis in patients with non-small cell lung cancer: A pilot study. (November 2019) - Szejniuk, W.M.; Nielsen, M.S.; Brønnum, D.; Takács-Szabó, Z.; Weinreich, U.M.; Pilegaard Thomsen, L.; Bøgsted, M.; Jensen, I.; McCulloch, T.; Falkmer, U.G.; Carl, J.; Røe, O.D.
Highlights: Weekly FeNO during radiotherapy can be useful in predicting radiation pneumonitis. 6 months of clinical follow-up is necessary to detect delayed radiation pneumonitis. Pulmonary function tests are not predictable for radiation pneumonitis. Abstract: Introduction: The aim of the study was to investigate repetitive fractional exhaled nitric oxide (FeNO) measurements during high-dose radiation therapy (HDRT) and to evaluate the use of FeNO to predict symptomatic radiation pneumonitis (RP) in patients being treated for non-small cell lung cancer (NSCLC). Materials and methods: A total of 50 patients with NSCLC referred for HDRT were enrolled. FeNO was measured at baseline, weekly during HDRT, one month- and every third month after HDRT for a one-year follow-up period. The mean FeNO(visit 0-6) was calculated using the arithmetic mean of the baseline and weekly measurements during HDRT. Patients with grade ≥ 2 of RP according to the Common Terminology Criteria for Adverse Events (CTCAE) were considered symptomatic. Results: A total of 42 patients completed HDRT and weekly FeNO measurements. Grade ≥ 2 of RP was diagnosed in 24 (57%) patients. The mean FeNO(visit 0-6)  ± standard deviation in patients with and without RP was 15.0 ± 7.1 ppb (95%CI: 12.0–18.0) and 10.3 ± 3.4 ppb (95%CI: 8.6–11.9) respectively with significant differences between the groups (p = 0.0169, 95%CI: 2.3–2.6). The leave-one-out cross-validated cut-off value of the mean FeNO(visit 0-6)  ≥ 14.8 ppb was predictive of grade ≥ 2 RP with a specificity of 71% and a positive predictive value of 78%. Conclusions: The mean FeNO(visit 0-6) in patients with symptomatic RP after HDRT for NSCLC was significantly higher than in patients without RP and may serve as a potential biomarker for RP.